Assessment of MRI image quality for various setup positions used in breast radiotherapy planning. Issue 1 (April 2016) - Batumalai, Vikneswary; Liney, Gary; Delaney, Geoff P.; Rai, Robba; Boxer, Miriam; Min, Myo; Berry, Megan; Pham, Trang; Phan, Penny; Choong, Callie; Rennie, Melanie; Chan, Christine; et al.
Abstract: This study investigates breast magnetic resonance imaging (MRI) image quality for 3 different breast radiotherapy positions (prone, supine flat and supine inclined) and associated choice of breast coils. Supine breast MRI has comparable image quality to prone breast MRI for the purposes of radiotherapy delineation for T2-weighted sequences.